2009
DOI: 10.1521/aeap.2009.21.3_supp.94
|View full text |Cite
|
Sign up to set email alerts
|

Medication Adherence in HIV-Infected Smokers: The Mediating Role of Depressive Symptoms

Abstract: Strict medication adherence is integral to the success of highly active antiretroviral therapies (HAART) in patients with HIV. Research has examined several predictors of adherence, but few studies have examined the association between current smoking, which is highly prevalent among people living with HIV, and medication adherence; moreover, no study has examined the mediating role of depressive symptoms, which may influence both smoking and adherence. Therefore, we recruited 168 patients who were prescribed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 57 publications
4
40
0
Order By: Relevance
“…The study assessed viral load, CD4+ count, cigarette smoking, and the past week and 3-month medication adherence. 68 The study found that 70% of participants smoked at least one cigarette per day, and smoking was associated with poorer past week and 3-month medication adherence. 3 In a study of HIV-positive men and women (n = 64), current cigarette smoking, lower CD4 counts and lower educational status emerged as independent predictors of poorer adherence among patients on HAART.…”
Section: Association Between Smoking and Increased Disease Activity Imentioning
confidence: 93%
“…The study assessed viral load, CD4+ count, cigarette smoking, and the past week and 3-month medication adherence. 68 The study found that 70% of participants smoked at least one cigarette per day, and smoking was associated with poorer past week and 3-month medication adherence. 3 In a study of HIV-positive men and women (n = 64), current cigarette smoking, lower CD4 counts and lower educational status emerged as independent predictors of poorer adherence among patients on HAART.…”
Section: Association Between Smoking and Increased Disease Activity Imentioning
confidence: 93%
“…Smoking during pregnancy is associated with a threefold increase in the risk of vertical HIV transmission [49]. Smoking is also correlated with lower drug adherence [50].…”
Section: Impact Of Continued Smokingmentioning
confidence: 99%
“…Smoking can be a response to negative feelings and mood states (Feldner, Babson, & Zvolensky, 2007;Reynolds, Neidig, & Wewers, 2004), and depression has been linked to smoking in an HIV-positive sample (Webb, Vanable, Carey, & Blair, 2009). Furthermore, psychological stresses associated with military training and deployment have been cited by soldiers as a motivation to smoke (Nelson et al, 2009;Stein et al, 2008).…”
Section: Original Investigation Present and Past Influences On Currenmentioning
confidence: 99%